The integration of docetaxel into first-line chemotherapy for ovarian cancer. (1st July 2001) - Kaye, S. B.
Abstract : Kaye SB. The integration of docetaxel into first-line chemotherapy for ovarian cancer. Docetaxel is being explored as an alternative to paclitaxel in the treatment of ovarian cancer for several reasons: a) evidence of superiority in preclinical models; b) at least comparable activity in platinum-refractory patients (28% response rate in four pooled Phase II trials), together with activity (23% response rate) in paclitaxel-refractory patients; c) indirect evidence of superiority in breast cancer; d) easier administration, ie, 1 h q3 week schedule vs. 3 or 24 h infusions; and e) potentially superior toxicity profile, particularly regarding neurotoxicity. The Scottish Gynaecological Cancer Trials Group (SGCTG) has performed successive first-line feasibility trials of docetaxel in combination with cisplatin (100 patients) and carboplatin (141 patients). For docetaxel/carboplatin, a regimen of 75 mg/m 2 and AUC 5 proved optimal. Over 90% of patients completed six cycles, q3 weekly, and toxicity was very acceptable; a low level of neurotoxicity (5%) was particularly noteworthy, since levels of over 30% are regularly reported for paclitaxel-carboplatin. Activity comparable to paclitaxel-carboplatin (median progression free survival of 16 months) therefore justified a randomized comparison between the two regimens (with paclitaxel 175 mg/m 2 in 3 h and carboplatin AUC 5). This has now been completed, with 1077 patients (FIGO stage IC-IV disease) randomized, from 83 centers in 10 countries. Accrual was accomplished in 17 months (October 1998 to May 2000). A toxicity analysis has been completed, since the last patient finished treatment in October 2000. Treatment was delivered as prescribed (6 cycles) in a similar number of patients (79–84%). Significant differences in toxicity were seen, and this analysis together with response data is scheduled for presentation at the May 2001 ASCO meeting.